Anecdotes in Youtube Videos in Javanese "Cenut Nut" (Sociolinguistic Study) - Masluchah, Umi Nur Laili; Supriyanto, Teguh (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia)
The purpose of this study is to analyze the form of language; to identify the language function; and to describe the characteristics of an anecdote message on YouTube video in Javanese Cenut Nut. This type of research is a qualitative descriptive study. The results of this study indicate the form or variation of anecdotal language in the Javanese Cenut Nut youtube video based on its speakers consisting of idiolects, dialects, and sociolects. The language function in the Cenut Nut youtube video, i.e. language expressed the speaker's feelings; language sought someone to do something; the language provides information; to express about the language itself; focus on the aesthetic value of language; and expressing solidarity and empathy for others. Characteristics of messages in the Java Cenut Nut youtube video are be known clearly (explicit) in the form of exclamations, advice, warnings, suggestions, or prohibitions relating to the main theme of a story; be conveyed directly or implied through characters or characterizations in a story; delivered in accordance with the phenomena in the community; the speakers often repeat words; the tone of speech used by the speaker tends to go up or rough; and the language used by the speaker were some words that contain pornographic associations. Based on the description above it can be concluded that in the Cenut Nut youtube video some forms or variations of language, language functions, and characteristics of messages that are different from Javanese in general.